Lived Experiences of ICU Nurses in Controlling Healthcare-Associated Infections - Magdy Nabil Maher Eryan; Ma. Julita Sibayan; Beryl Ben Mergal; Joyosthie Orbe (International Journal of Public Health and Nursing, 2026)
Healthcare-associated infections (HCAIs) remain a persistent challenge in intensive care units (ICUs), contributing to increased morbidity, mortality, and healthcare expenditures. Despite established infection prevention and control (IPC) protocols, gaps persist between institutional policies and actual nursing practices, particularly in resource-constrained healthcare settings. Limited qualitative evidence from the Philippines highlights the need to understand the lived experiences of ICU nurses in controlling healthcare-associated infections within clinical environments. This study explored the lived experiences of ICU nurses in controlling healthcare-associated infections in selected tertiary care hospitals in the Philippines. An exploratory-descriptive qualitative design grounded in descriptive phenomenology was utilized. Registered ICU nurses with 2–5 years of clinical experience were recruited through snowball sampling until data saturation was achieved. Data saturation was reached during the eighth interview, after which two additional interviews were conducted to confirm the recurrence of themes, resulting in a total of ten participants. Data was collected through semi-structured online interviews. Bracketing, member checking, and investigator triangulation were employed to ensure rigor and trustworthiness. Data were analyzed using Colaizzi’s phenomenological method. Three overarching themes emerged. Infection Prevention as an Organizing Framework of Care illustrated how protocols and collaborative endeavors shape daily practice despite occupational depletion. Permeative Vigilance described infection prevention as an embedded ethical orientation sustained through habituation and reciprocal preservation. Cumulative Clinical Evolution reflected the progressive advancement of practices through continuous learning and technological opportunities. Collectively, these themes demonstrate that infection prevention is integrated into nurses’ professional identity and ethical accountability.